1977
DOI: 10.1017/s0031182000048307
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigations on the behaviour of the cercariae of an ectoparasitic digenean transversotrema patialense: general activity patterns

Abstract: The activity patterns of the cercariae of Transversotrema patialense have been examined by monitoring the behaviour of individual larvae. Records of three different behavioural modes, namely active, tail–first swimming, passive dropping and resting periods were made separately. The age- and temperature–dependence of the activity patterns during the spontaneously active life of the cercariae were examined and estimates made of the absolute speeds of swimming and dropping. Through the temperature range 25–32° C,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
1

Year Published

1978
1978
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 16 publications
2
14
1
Order By: Relevance
“…This study confirms Chapman's (1974) observation that with age, the length of active periods declined while inactive periods increased. These findings are in contrast to those of Whitfield et al (1977) who reported that the mean duration of swimming and dropping events of T. patialense did not alter significantly during ageing. The discrepancy in the behaviour of the cercariae can now be firmly attributed to inter-species differences.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…This study confirms Chapman's (1974) observation that with age, the length of active periods declined while inactive periods increased. These findings are in contrast to those of Whitfield et al (1977) who reported that the mean duration of swimming and dropping events of T. patialense did not alter significantly during ageing. The discrepancy in the behaviour of the cercariae can now be firmly attributed to inter-species differences.…”
Section: Discussioncontrasting
confidence: 99%
“…He found that the behaviour of the cercariae consists of short upwardly directed swimming bursts alternating with longer periods of sinking or resting. Whitfield, Anderson & Bundy (1977), however, pointed out that because of the design of the apparatus, in some experiments it was not possible to differentiate between sinking and resting events. In these experiments the cercariae were confined to a 2 mm high horizontal cell and were photographed from above.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Larvae live freely in the water column before they attach to their terminal host, which they locate from host-derived chemical or mechanical cues, or shadows (Whittington et al 2000). Attachment typically occurs during seasonal epizootic events, which are characterised by cool (~ 25 °C) or warm (~ 32 °C) water conditions (Whitfield et al 1977) and may coincide with a time when hosts are particularly vulnerable to infection (Möller 1978;Silan et al 1983;Tubbs et al 2005;Rückert et al 2008). We conjecture for further study that the seasonality with which giant manta rays visit Monad Shoal might coincide with ectoparasite attachment events in the area, leading to heightened parasitism and a greater need for interacting with cleaners.…”
Section: Cleaning Interactionsmentioning
confidence: 99%